2013
DOI: 10.1007/s11270-013-1549-6
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and Chlorinated Pesticides on the Highest Level of the Food Web as Exemplified by Herring from the Southern Baltic and African Penguins from the Zoo

Abstract: Aquatic birds are often used as a health indicator of the marine ecosystem. African penguins living in the zoo make good research material as they form a link between the marine and the terrestrial ecosystem in terms of xenobiotic circulation. Tests were performed on whole herring—the food of the penguins—as well as on bird muscle, liver, brain, eggs, feathers and guano in order to determine total mercury, aldrin, dieldrin, endrin, isodrin, endosulfan isomers, endosulfan sulfate, methoxychlor, dichlorodiphenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 23 publications
3
20
2
Order By: Relevance
“…Several pesticides have been analysed in feathers, including OC in both terrestrial and aquatic species; however, the scientific literature on this subject is still developing (García-Fernández et al, 2013). Furthermore, studies analyzing these contaminants in feathers have covered species from very few locations such as Belgium, southwest Iran, southeast Spain, the Baltic region and South India (Behrooz et al, 2009a, b;Espín et al, 2012;Falkowska et al, 2013;García-Fernández et al, 2013;Jaspers et al 2004Jaspers et al , 2007Tanabe et al, 1998) but there is no information on such in the area of this study. Although there is information on trace elements in feathers of Turkey vulture in North America (Cahill et al, 1998;Haskins et al, 2013), to our knowledge, this is the first study on OC in feathers of raptor species from Southern South America.…”
Section: Introductionmentioning
confidence: 99%
“…Several pesticides have been analysed in feathers, including OC in both terrestrial and aquatic species; however, the scientific literature on this subject is still developing (García-Fernández et al, 2013). Furthermore, studies analyzing these contaminants in feathers have covered species from very few locations such as Belgium, southwest Iran, southeast Spain, the Baltic region and South India (Behrooz et al, 2009a, b;Espín et al, 2012;Falkowska et al, 2013;García-Fernández et al, 2013;Jaspers et al 2004Jaspers et al , 2007Tanabe et al, 1998) but there is no information on such in the area of this study. Although there is information on trace elements in feathers of Turkey vulture in North America (Cahill et al, 1998;Haskins et al, 2013), to our knowledge, this is the first study on OC in feathers of raptor species from Southern South America.…”
Section: Introductionmentioning
confidence: 99%
“…The average daily doses (± SD) of HBCD and TBBPA were estimated at 252.9 ± 113.7 and 26.3 ± 14.9 ng, respectively. Results presented by Falkowska et al ( 2013 ) have already showed that daily exposure of mercury and chlorinated organic compounds by way of diet vary greatly. The performed analysis has shown the presence of brominated compounds in the tissues and organs of penguins from the zoo with the highest BFRs concentrations occurring in the brain of a relatively old female (age 8 years 7 months) (Table 1 ).…”
Section: Resultsmentioning
confidence: 96%
“…Sometimes, up to 5 -20% of the contaminants present in their diet could be eliminated via egg laying (Falkowska et al, 2013). Given the relatively high total Hg levels observed in the present study, especially for the crane species, it remains unclear whether this elimination mechanism is an important adaptation strategy adopted by the birds to alleviate the detrimental effects of Hg.…”
Section: Assessing Ecological Risks Associated With Hg Levels In Invementioning
confidence: 83%